RELASI SEMANTIK KATA BAHASA DAYAK KANAYATN - Arhami Khuzaifah; Hotma Simanjuntak; Agus Syahrani (Universitas Tanjungpura, 2019)
ABSTRACTThe method that used in this research was description method with qualitative from research. The data source in this research was the native speaker of Dayak Kanayatn people that represented by informant and obtained through the observation and direct field recording. The data ini this research was about synonym, antonym, polysemy, hyponym and homonym. The technique that used in this research was direct technique, listening tehnique, capable technique and documenter study technique. The data collection tool was a list of questions a list of picture folklore, data card. In the synonym and polysemy has produce a relation because there are form and meaning. The synoym has a different form but same meaning, meanwhile polysemy has a same form but different meaning, so that’s way relation happen between both of them. Hyponym and antonym has produce a relation because there are two meaning, hyponym has a meaning that covers other meaning, meanwhile antonym has a meaning in out of other meaning so that’s why both of them have a relation. Homonym has produce a relation because there are two form, homonym has a same from but different meaning. So that’s why the relation was happen between one of that form. Keyword: Semantic Relation Word, Synonym and Polysemy, Hyponym and antonym, homonym, Dayak Kanayatn Language.